Hospital volume and outcome in the treatment of congenital diaphragmatic hernia in Germany: observational study using national hospital discharge data from 2016 to 2023 - Elrod, Julia; Boettcher, Michael; Kipfmüller, Florian; Schaible, Thomas; Wolfram Trudo, Knoefel; Mohr, Christoph; Herwig, Ramona; Samans, Max; Busse, Reinhard; Nimptsch, Ulrike; Wilms, Miriam (Journal of pediatric surgery, 2025)
Background - Congenital diaphragmatic hernia (CDH) is a critical malformation, with the neonatal period being particularly challenging and associated with high mortality. Data on the care structure and volume-outcome relationship in the treatment of children with CDH in Germany remain scarce. - Methods - This study determined case numbers and outcomes of treatment of children aged 0-17 years, with CDH in Germany between 2016 and 2023 through a query of the nationwide DRG database at the Research Data Center of the Federal Statistical Office. Using the ICD-10 and OPS codes, inpatient cases with and without ECMO treatment were identified. The analysis included patient characteristics, hospital caseload, treatment characteristics and outcome parameters stratified by hospital caseload. - Results - In the 8 years, a total of 1470 newborns with CDH were born across 234 different hospitals, with a median annual caseload of 1 (IQR: 1-2). In-hospital mortality was 22.5 %. Corrective surgery was performed in 1539 cases across 103 hospitals. Mortality among patients who underwent corrective surgery was 4.8 % in low-volume centers, 5.3 % in medium-volume centers, and 9.6 % in high-volume centers. A higher ECMO frequency was observed in high-volume centers (32.2 % vs. 5.4 % in medium-volume and 1.9 % in low-volume). Among all ECMO-treated CDH patients, regardless of corrective surgery, mortality was 60.0 %, 40.0 %, and 36.5 % in low-, medium-, and high-volume centers, respectively. - Conclusions - These findings indicate that high-volume centers treat a greater proportion of severe cases and that they may achieve better outcomes for the most critically ill patients, as reflected by lower ECMO-specific mortality.
Online verfügbar: 7. Juni 2025, Artikelversion: 18. Juni 2025
Gesehen am 19.08.2025